2021
DOI: 10.3390/app11051982
|View full text |Cite
|
Sign up to set email alerts
|

Novel Structures and Applications of Graphene-Based Semiconductor Photocatalysts: Faceted Particles, Photonic Crystals, Antimicrobial and Magnetic Properties

Abstract: Graphene, graphene oxide, reduced graphene oxide and their composites with various compounds/materials have high potential for substantial impact as cheap photocatalysts, which is essential to meet the demands of global activity, offering the advantage of utilizing “green” solar energy. Accordingly, graphene-based materials might help to reduce reliance on fossil fuel supplies and facile remediation routes to achieve clean environment and pure water. This review presents recent developments of graphene-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 181 publications
(235 reference statements)
0
13
0
Order By: Relevance
“…It has high thermal and electrical conductivity, provides a barrier against gases and has the ability to absorb visible and near-infrared light [ 22 , 23 ]. It can also be easily stretched and coated on the surface of various materials and in different forms, and recent studies have also confirmed its bactericidal and bacteriostatic properties [ 6 , 24 , 25 ]. These unique properties mean that graphene has great potential and it has already been successfully applied in many fields, such as the automotive industry, aerospace, electrical engineering, robotics, solar cells, energy storage, telecommunications, biochemistry and medicine [ 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has high thermal and electrical conductivity, provides a barrier against gases and has the ability to absorb visible and near-infrared light [ 22 , 23 ]. It can also be easily stretched and coated on the surface of various materials and in different forms, and recent studies have also confirmed its bactericidal and bacteriostatic properties [ 6 , 24 , 25 ]. These unique properties mean that graphene has great potential and it has already been successfully applied in many fields, such as the automotive industry, aerospace, electrical engineering, robotics, solar cells, energy storage, telecommunications, biochemistry and medicine [ 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…What is more important, the photogenerated electrons can migrate only from ferrite to carbon material. In this regard, the main shortcoming of a ferrite-based photocatalyst, i.e., photobleaching, is inhibited [63].…”
Section: Spinel Ferrite Compositesmentioning
confidence: 99%
“…Accordingly, the co-infection awareness in relation to COVID-19 disease has forced researchers to look for possible solutions, obviously including methods that have already been applied to prevent the growth of bacteria and fungi or as antiviral agent (e.g., carbon-based nanomaterials) [ 8 , 9 , 10 ]. For example, photocatalysis has proven to be highly efficient to inactivate various microorganisms, resulting even in their complete decomposition (mineralization) [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%